NOFILOLOGIK YO‘NALISHLARDA CHET TILINI O‘QITISH METODIKASI - To‘xtaboyev Dilshodbek Sobirovich,; Maksudova Hilola Ferdinandovna, (TADQIQOTLAR, 2026)
This  article  examines  the  theoretical  and  practical  foundations  of  teaching  a foreign language to students of non-philological fields. In particular, the effectiveness of professionally oriented foreign language education, the formation of communicative competence, CLIL (Content and Language Integrated Learning) methodology, as well as  interactive  and  innovative  teaching  methods,  are  analyzed.  In  addition,  modern approaches  to  foreign  language  teaching  through  the  use  of  information  and communication technologies are highlighted.